Analisis Perbandingan Efektivitas Metode Langsung dan Tidak Langsung dalam Penyusunan Anggaran Kas dalam Upaya Menjaga Likuiditas Perusahaan - Johs Charlos Hutabalian; Herlina Bernadecka Sidauruk (Jurnal Ilmu Ekonomi dan Bisnis, 2026)
This study aims to compare the effectiveness of the direct method and the indirect method in preparing cash budgets to maintain corporate liquidity. The research uses a qualitative method with a systematic literature review approach, analyzing ten journal articles published between 2020 and 2026. The findings indicate that the direct method is more effective than the indirect method because it presents detailed cash receipts and disbursements transparently, enables early detection of cash deficits, provides tighter expenditure control, and delivers more relevant information for decision-making. In contrast, the indirect method, used by almost all companies (99.9%) due to cost efficiency and convenience, is considered less effective for maintaining liquidity as the information it provides is aggregated. This study concludes that the direct method is superior for maintaining liquidity, especially for MSMEs and manufacturing companies. The main recommendation is to encourage companies to adopt the direct method or at least provgross cash disclosures in financial statements.